2013
DOI: 10.1097/sle.0b013e31828e375c
|View full text |Cite
|
Sign up to set email alerts
|

An Elusive Etiology of Upper Gastrointestinal Bleeding in a Young Man

Abstract: Herein, we present a case of testicular tumor in a young patient in whom the initial symptom was upper gastrointestinal bleeding secondary to duodenal invasion by retroperitoneal lymph node involvement. Although melanoma, renal, breast, bronchogenic, and gastric carcinoma are the most common metastatic tumors of the small bowel, testicular tumors should be considered in the differential diagnosis of duodenum invasion in a young man because they are the most common tumor in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The first hypothesis suggests that metastases may occur via the lymph drainage duct to the testis and epididymis. Gastric metastases have also been reported to originate from testicular cancer, probably via invasion of the stomach by testicular cancer through lymphatic ducts[ 13 - 15 ]. It is reported that testicular and gastric cancers have overlapping lymphatic metastasis pathways[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis suggests that metastases may occur via the lymph drainage duct to the testis and epididymis. Gastric metastases have also been reported to originate from testicular cancer, probably via invasion of the stomach by testicular cancer through lymphatic ducts[ 13 - 15 ]. It is reported that testicular and gastric cancers have overlapping lymphatic metastasis pathways[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma, renal, mammary, bronchopulmonary, gastric or testicular neoplasia[ 4 ] represent the most frequent metastatic tumours at the level of the small bowel, and particularly at the level of the duodenum. However, in young men, a testicular origin is to be favoured due to the preferential epidemiology of these cancers in this population group[ 1 ].…”
Section: Discussionmentioning
confidence: 99%